EXPERIMENTAL IN HEAD TRACKING CONTROL OF A FOUR OMNI WHEELED MOBILE ROBOT SYSTEM - Srun Channareth; Lonh Vannsith; Ny Virbora (Indonesian Journal of Engineering and Science, 2022)
This article describes an experimental investigation into the head tracking and control of a four-wheeled Omni-Robot. This study described the control scheme of the omnidirectional mobile robot. Additionally, the kinematics of the mobile robot is presented., A mobile robot with four Omni wheels was also developed on real hardware to verify the controller architecture design. The robot system is modeled and then implemented with the Arduino Microcontroller. This robot has two rotary encoders for running on the x-axis and y-axis, respectively. The gyro sensor (MPU-6050) is placed in the robot's middle and tracks data obtained by yaw angle. MATLAB Simulink was used to find the PD controller based on manual adjustment. The control architecture was deployed to complete and run the experiment on the mobile robot to evaluate the outcomes. The experiment results show the robot's motion control improvement in various scenarios.